2001
DOI: 10.1128/aac.45.1.267-274.2001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Current Activities of Fluoroquinolones against Gram-Negative Bacilli Using Centralized In Vitro Testing and Electronic Surveillance

Abstract: Given the propensity for Enterobacteriaceae and clinically significant nonfermentative gram-negative bacilli to acquire antimicrobial resistance, consistent surveillance of the activities of agents commonly prescribed to treat infections arising from these organisms is imperative. This study determined the activities of two fluoroquinolones, levofloxacin and ciprofloxacin, and seven comparative agents against recent clinical isolates of Enterobacteriaceae, Pseudomonas aeruginosa, Acinetobacter baumannii, and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
43
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 31 publications
(69 reference statements)
5
43
4
Order By: Relevance
“…Quinolones are among the most commonly prescribed antimicrobials for the treatment of serious infections caused by E. cloacae and other members of the Enterobacteriaceae family. However, the development of resistance to these antibiotics in the causative bacteria has complicated treatment and may lead to treatment failures (30) . In recent years, PMQR has been reported in several studies, especially in enterobacteria (8) .…”
Section: Discussionmentioning
confidence: 99%
“…Quinolones are among the most commonly prescribed antimicrobials for the treatment of serious infections caused by E. cloacae and other members of the Enterobacteriaceae family. However, the development of resistance to these antibiotics in the causative bacteria has complicated treatment and may lead to treatment failures (30) . In recent years, PMQR has been reported in several studies, especially in enterobacteria (8) .…”
Section: Discussionmentioning
confidence: 99%
“…The widespread use, more often the misuse, of antimicrobial drugs has led to a general rise in the emergence of resistant bacteria. It is reported that in the United State there is rise in the resistan t strains to ampicilli n due to its widesprea d use 14 . With this evidence from our study, we can suggest meropenem, amikacin, ceftazidime, gentamicin and imipenem to be prescribed as the empirical treatment for UTI.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of centralized in vitro studies conducted in the United States from 1997 to 2002 that have studied the susceptibility of P. aeruginosa (4,6,7,13,17). For the fluoroquinolones, it appears that susceptibility among P. aeruginosa isolates is decreasing in the United States (2,4,6,7,13,14,16), perhaps because of increasing or cumulative fluoroquinolone use, the lack of adherence to approved infection control prac- MDR (resistance to three or more antimicrobial agents) accounted for 24.9% of all isolates in this study. MDR was significantly higher for nursing home patients (29.9%) and ICU patients (29.5%) than for non-ICU patients and outpatients (P Ͻ 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Although several surveillance studies have reported on the relative in vitro activities of various antimicrobial agents (4,6,7,13,16), an extensive comparative statistical analysis of resistance to antimicrobial agents relative to factors associated with resistance has not been performed. Such analysis is important to more completely elucidate the status of antimicrobial resistance among P. aeruginosa isolates and to attempt to understand and predict the direction and chronology of future resistance trends.…”
mentioning
confidence: 99%